Utilising variable vector step-size in normalised LMS algorithm. (2nd September 2011) - Li, Ning; Zhang, Yonggang; Hao, Yanling
A new variable step-size normalised least mean square (NLMS) algorithm is proposed in this paper, which is designed for the applications where the unknown filter has an exponential decay impulse response. In the proposed algorithm, a variable vector step-size is used on the basis of maximising the decrease of the mean square deviation (MSD). Theoretical analysis is given to show the validity. Compared with other variable step-size NLMS algorithms, the proposed method has a faster convergence rate and smaller steady state mean square error (MSE). Simulation results show the improved performance of the proposed algorithm. The same idea of utilising variable vector step-size can be expanded to other variable step-size NLMS algorithms.